Arch, David Sassoon Clock Tower - Ghosh, Ayan (2023)
Arch and keystone detail with panels of Minto tiles and dressings of Blashfield's terracotta from Stamford, Lincolnshire. The clock tower is built from Porbandar stone, which was used in many public buildings in Mumbai, like the Chhatrapati Shivaji Maharaj Terminus, the Knesset Eliyahoo Synagogue, the Bombay High Court, and Crawford Market.